Smut infection of perennial hosts: the genome and the transcriptome of the Brassicaceae smut fungus Thecaphora thlaspeos reveal functionally conserved and novel effectors. Issue 3 (17th February 2019) - Courville, Kaitlyn J.; Frantzeskakis, Lamprinos; Gul, Summia; Haeger, Natalie; Kellner, Ronny; Heßler, Natascha; Day, Brad; Usadel, Björn; Gupta, Yogesh K.; van Esse, H. Peter; Brachmann, Andreas; Kemen, Eric; et al.
Summary: Biotrophic fungal plant pathogens can balance their virulence and form intricate relationships with their hosts. Sometimes, this leads to systemic host colonization over long time scales without macroscopic symptoms. However, how plant‐pathogenic endophytes manage to establish their sustained systemic infection remains largely unknown. Here, we present a genomic and transcriptomic analysis of Thecaphora thlaspeos . This relative of the well studied grass smut Ustilago maydis is the only smut fungus adapted to Brassicaceae hosts. Its ability to overwinter with perennial hosts and its systemic plant infection including roots are unique characteristics among smut fungi. The T. thlaspeos genome was assembled to the chromosome level. It is a typical smut genome in terms of size and genome characteristics. In silico prediction of candidate effector genes revealed common smut effector proteins and unique members. For three candidates, we have functionally demonstrated effector activity. One of these, Tt Tue1, suggests a potential link to cold acclimation. On the plant side, we found evidence for a typical immune response as it is present in other infection systems, despite the absence of any macroscopic symptoms during infection. Our findings suggest that T. thlaspeos distinctly balances its virulence during biotrophic growth ultimately allowing for long‐lived infection of its perennial hosts.